A systematic review and evaluation of inhibitory stimulus control procedures as a treatment for stereotyped behavior among individuals with autism. (17th November 2017) - Lydon, Sinéad; Moran, Laura; Healy, Olive; Mulhern, Teresa; Enright Young, Kerie
ABSTRACT: Purpose : Stereotypy is pervasive among persons with autism and may impact negatively on social inclusion and learning. The implementation of resource-intensive behavioral interventions to decrease these behaviors has been questioned. Inhibitory stimulus control procedures (ISCPs) comprise a type of antecedent-based intervention that has been proposed as an effective treatment approach for stereotypy but has received limited research attention to date. Method : The current systematic review sought to examine and synthesize the literature reporting applications of ISCPs in the treatment of stereotypy among persons with autism. Treatment outcomes were analyzed quantitatively and the status of ISCPs as evidence-based practice was evaluated in accordance with the National Autism Center's National Standards Report guidelines. Results : A total of 11 studies were reviewed with results indicating that ISCPs constituted an emerging treatment for the stereotypy exhibited by persons with autism. Conclusions : ISCPs comprise a promising intervention for stereotyped behavior but further research is required.